The Determinant Factors of Customer Loyalty: Service Quality and Customer Satisfaction - Ranu Tri Johan Efendi; Hermien Tridayanti; Joko Suyono; Damarsari Ratnasahara Elisabeth; Dian Arisanti (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: is to find out and analyze determine the effect of service quality on customer satisfaction, service quality on customer loyalty, customer satisfaction on customer loyalty and the role of customer satisfaction as a mediation of the effect of service quality on customer loyalty in Teluk Lamong loading and unloading container terminal. Design/methodology/approach: Design of this research uses quantitative research. Research limitations/implications: This research conducted on Teluk Lamong customers with include 229 respondents samples and are distributed through questionnaires, as well as the data results are processed using SEM PLS version 3.0. Practical implications: The results prove that there is a significant effect of service quality on customer satisfaction at PT Terminal Teluk Lamong. The second results imply that there is a significant effect of service quality on customer satisfaction at PT Terminal Teluk Lamong. Likewise, the effect of customer satisfaction on customer loyalty at PT Terminal Teluk Lamong is also significant. Satisfaction is also confirmed to mediate the effect of service quality on customer loyalty. Originality/value: This Paper Is Original Paper type: This paper can be categorized as case study paper.